A high-precision dry-pressing method for high-performance electronic insulating ceramic sheets
Patent Information
- Application Number
- CN202611233092.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-13
AI Technical Summary
随着压制压力升高,造粒颗粒虽然能够发生变形或局部破碎,但部分粘结剂富集界面仍可能沿原造粒颗粒边界连续保留
[0023]通过使致密陶瓷处理颗粒与喷雾造粒颗粒发生滚动接触,选择性磨除喷雾造粒颗粒外凸部位的含粘结剂表层,并保留相邻外凸部位之间的含粘结剂表层,使得喷雾造粒颗粒在保持装粉流动性和颗粒完整性的同时,能够在初压过程中通过陶瓷基料外露窗口形成无机陶瓷接触,并在主压过程中形成分散的陶瓷粉体连接位置,从而解决了原造粒颗粒接触界面因粘结剂富集而形成连续孔隙、导致烧结收缩和绝缘性能不均的问题。
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic insulating ceramic sheet technology, and more specifically, to a high-precision dry pressing method for high-performance electronic insulating ceramic sheets. Background Technology
[0002] Electronic insulating ceramic sheets are typically made from insulating ceramic powders such as alumina as the base material, through processes including slurry preparation, spray granulation, powder loading, dry pressing, binder removal, and sintering. Spray granulation improves the flowability and loading stability of the ceramic powder; however, to ensure the integrity of the granulated particles during conveying, loading, and demolding, a certain amount of binder is usually added to the granulation slurry. During spray drying, the binder tends to migrate with the liquid phase towards the surface of the granulated particles, resulting in a higher binder content on the outer surface than inside the particles.
[0003] During dry pressing, adjacent granulated particles first come into contact at the convex portions of their respective surfaces. When these convex portions are still covered with a binder-rich surface layer, a contact interface separated by the binder easily forms between adjacent granulated particles. As the pressing pressure increases, although the granulated particles may deform or partially break, some binder-rich interfaces may still remain continuously along the original granulated particle boundaries. During subsequent binder removal, the organic matter at the interface is easily burned off, forming continuous or semi-continuous pores. During sintering, these pores may be difficult to completely close due to insufficient contact with local ceramic powder, resulting in inconsistent local shrinkage and affecting the uniformity of the ceramic sheet's thickness, flatness, and insulation performance.
[0004] Existing processes typically improve compaction by increasing pressing pressure, reducing binder dosage, or adjusting granulation particle strength. However, increasing pressing pressure makes it difficult to directly eliminate the binder isolation layer located at the particle contact position, while reducing the overall binder dosage weakens the conveying strength, powder flowability, and green strength of the granulated particles.
[0005] Therefore, how to ensure that the initial contact position of the granulated particles forms direct contact with the ceramic matrix while retaining most of the binder-containing surface layer of the granulated particles, and reduce the formation of continuous pores at the boundary of the original granulated particles, is one of the urgent problems to be solved in the dry pressing process of electronic insulating ceramic sheets. Summary of the Invention
[0006] To address the problems mentioned in the background section, the present invention provides the following technical solution:
[0007] A high-precision dry pressing method for high-performance electronic insulating ceramic sheets includes:
[0008] Electronic insulating ceramic matrix, sintering aid and binder are mixed to form ceramic slurry, and the ceramic slurry is spray-dried to obtain spray-granulated particles with the binder on the surface;
[0009] The spray-granulated particles are mixed with the dense ceramic treated particles, so that the spray-granulated particles and the dense ceramic treated particles come into rolling contact. The main crystal phase composition of the dense ceramic treated particles is the same as that of the main crystal phase composition of the electronic insulating ceramic matrix.
[0010] The degree of rolling contact is controlled so that the binder-containing surface layer of the protruding part of the spray granulation particle is partially ground away to expose the electronic insulating ceramic matrix, while the binder-containing surface layer between adjacent protruding parts is retained, forming multiple mutually separated ceramic matrix exposure windows on the surface of the spray granulation particle, and keeping the spray granulation particle with an intact granulation particle shape.
[0011] The dense ceramic treated particles and the free fine powder that detached during the rolling contact process were separated from the treated spray granulated particles to obtain the contact window granulated material.
[0012] The granulated material with the contact window is filled into the molding cavity and initially pressed, so that at least some of the adjacent sprayed granulated particles form ceramic matrix contact through the exposed ceramic matrix window located on their respective convex parts;
[0013] Continue to increase the pressing pressure to deform or break the spray-granulated particles and cause the ceramic powder around the exposed window of the ceramic matrix to interlock with each other, thereby obtaining an electronic insulating ceramic green body;
[0014] The electronic insulating ceramic green body is depressurized and demolded.
[0015] Furthermore, the dense ceramic treated particles are sintered ceramic particles with a higher degree of density than the spray-granulated particles, and do not break during the rolling contact process.
[0016] Furthermore, the particle size of the dense ceramic treated particles is larger than that of the spray granulation particles, so that after the rolling contact is completed, the dense ceramic treated particles can be separated from the treated spray granulation particles by sieving.
[0017] Furthermore, the exposed windows of the ceramic matrix are spaced apart from each other, and the binder-containing surface layer between adjacent exposed windows of the ceramic matrix extends continuously to maintain the particle integrity of the spray-granulated particles during the conveying, powder loading and initial pressing processes.
[0018] Furthermore, during the rolling contact process, the dense ceramic treated particles preferentially contact the convex portion of the spray-granulated particles, and the rolling contact is stopped before the spray-granulated particles disintegrate into primary ceramic powder.
[0019] Furthermore, when separating the dense ceramic treated particles and free fine powder from the treated spray granulation particles, the dense ceramic treated particles are first removed by sieving, and then the free fine powder that is not bound to the spray granulation particles is removed by airflow separation.
[0020] Furthermore, the initial pressure causes adjacent spray-granulated particles to come into contact with each other and maintains the overall outline of most spray-granulated particles; after the initial pressure, the pressing pressure is further increased to deform or break the spray-granulated particles and to form multiple ceramic powder connection positions formed by the exposed windows of the ceramic matrix between adjacent spray-granulated particles.
[0021] Furthermore, the electronic insulating ceramic matrix is an alumina ceramic matrix or an aluminum nitride ceramic matrix, and the dense ceramic treated particles are dense alumina ceramic particles or dense aluminum nitride ceramic particles.
[0022] In summary, the present invention has the following beneficial effects:
[0023] By making dense ceramic treated particles roll into contact with spray-formed particles, the binder-containing surface layer on the protruding parts of the spray-formed particles is selectively ground away, while the binder-containing surface layer between adjacent protruding parts is retained. This allows the spray-formed particles to maintain powder flowability and particle integrity, while forming inorganic ceramic contact through the exposed windows of the ceramic matrix during the initial pressing process, and forming dispersed ceramic powder connection positions during the main pressing process. This solves the problem of continuous pores formed at the original granulation particle contact interface due to binder enrichment, which leads to sintering shrinkage and uneven insulation performance. Detailed Implementation
[0024] Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Example:
[0026] This invention provides a technical solution: a high-precision dry pressing molding method for high-performance electronic insulating ceramic sheets, comprising: mixing electronic insulating ceramic base material, sintering aid and binder to form a ceramic slurry, spray drying the ceramic slurry to obtain spray-granulated particles with binder on the surface;
[0027] The spray-granulated particles are mixed with the dense ceramic treated particles, so that the spray-granulated particles and the dense ceramic treated particles come into rolling contact. The main crystal phase composition of the dense ceramic treated particles is the same as that of the main crystal phase composition of the electronic insulating ceramic matrix.
[0028] By controlling the degree of rolling contact, the binder-containing surface layer of the outward protrusion of the spray-granulated particles is partially ground away to expose the electronic insulating ceramic matrix, while the binder-containing surface layer between adjacent outward protrusions is retained, forming multiple mutually separated ceramic matrix exposure windows on the surface of the spray-granulated particles, and maintaining the complete granulation particle shape of the spray-granulated particles.
[0029] The dense ceramic particles and the free fine powder that detached during the rolling contact process were separated from the treated spray granulated particles to obtain the contact window granulated material.
[0030] The contact window granules are filled into the molding cavity and initially pressed so that at least some of the adjacent spray granules form ceramic matrix contact through the exposed ceramic matrix windows located on their respective convex parts.
[0031] Continue to increase the pressing pressure to deform or break the spray-granulated particles and cause the ceramic powder around the exposed window of the ceramic matrix to interlock with each other, thus obtaining an electronic insulating ceramic green body.
[0032] Depressurize and demold the electronic insulating ceramic green body;
[0033] In this embodiment: 96 alumina electronic insulating ceramic sheet was prepared by using alumina powder with a median particle size of 0.8 μm as the ceramic matrix and adding a sintering aid composed of silicon dioxide, magnesium oxide and calcium carbonate. The alumina powder accounted for 96.2% of the total mass of the inorganic powder and the sintering aid accounted for 3.8% of the total mass of the inorganic powder.
[0034] Inorganic powder, polyvinyl alcohol binder, polyethylene glycol plasticizer, ammonium polyacrylate dispersant, and deionized water were mixed and ball-milled for 18 h. The amounts of polyvinyl alcohol, polyethylene glycol, and ammonium polyacrylate added were 2.4%, 0.6%, and 0.3% of the inorganic powder mass, respectively. After ball milling, the solid content of the slurry was adjusted to 63%, and then filtered through a 120-mesh sieve to improve the dispersion uniformity of each component in the slurry and reduce the local enrichment of binder during spray granulation.
[0035] The filtered slurry was granulated using a centrifugal spray dryer. The inlet air temperature was set to 185℃, the outlet air temperature was controlled between 92 and 98℃, and the atomizing disc speed was set to 9000 r / min. After sieving, the resulting granules retained a portion with a particle size of 55–125 μm, with a loose density of 1.12 g / cm³ and a moisture content of 0.42%. When 100 granules were randomly selected for observation, 98 of them were intact, ensuring that the resulting granules maintained stable flowability and consistent powder filling.
[0036] Spherical ceramic particles with a diameter of 0.6 to 0.9 mm were prepared using the same inorganic composition as the alumina ceramic matrix mentioned above, and sintered at 1580℃ to a relative density of not less than 95%, resulting in dense ceramic particles with smooth surfaces that are not easily broken. This avoids the introduction of heterogeneous wear debris during the rolling process or the increase of free fine powder due to the breakage of the treated particles themselves.
[0037] Spray-granulated granules and dense ceramic-treated granules are added to a horizontal drum lined with an alumina ceramic layer at a mass ratio of 4:1. The total volume of the material in the drum accounts for 35% of the effective volume of the drum. The drum is then rolled at 12 r / min for 5 min to allow the dense ceramic-treated granules to roll and intermittently contact the granulated granules.
[0038] During the rolling contact process, the convex parts of the spray-granulated particle surface that first come into contact with the dense ceramic treated particle are subjected to slight friction, causing the binder-rich surface layer at the convex parts to be partially worn away and exposing the alumina matrix. Meanwhile, the surface layer between adjacent convex parts retains the binder, thus forming multiple separate ceramic matrix exposed positions without destroying the overall morphology of the granulated particles.
[0039] During the rolling process, samples were taken every 1 minute, and 30 randomly selected granulated particles were observed using a scanning electron microscope. The process was stopped when the surface of the granulated particles showed rough exposed areas that were separated from each other, while the smooth surface layer was still retained between adjacent exposed areas, and the number of intact particles was not less than 29. In this embodiment, the average proportion of the exposed area of the ceramic matrix to the surface area of the granulated particles was 18.6%.
[0040] By controlling the formation range of the exposed area of the ceramic matrix, the granulated particles can still maintain their strength by relying on the retained binder surface layer during transportation and powder loading. At the same time, the convex position can preferentially form inorganic ceramic contact points during subsequent initial pressing, avoiding continuous adhesion of the binder-rich surface layer of adjacent granulated particles at the stress contact position.
[0041] After processing, the dense ceramic particles are first separated using a sieve with a pore size of 300 μm. Then, the granules under the sieve are passed through an airflow sorting channel with a wind speed of 1.8 m / s to remove free fine powder that has fallen off during the rolling process and has not been combined with the granules. The mass percentage of free fine powder with a particle size of less than 20 μm in the resulting granules is 0.21%.
[0042] By removing dense ceramic particles and free fine powder, the powder entering the mold cavity still uses intact spray-formed granulated particles as the main flow unit, reducing the impact of free fine powder on the flowability of the granulated material, the uniformity of powder loading in the mold cavity, and the local density of the green body. This also ensures that the subsequent technical effects mainly come from the exposed ceramic matrix on the surface of the granulated particles.
[0043] The processed granules are loaded into a square mold cavity with a length of 50 mm and a width of 50 mm. After being leveled, they are initially pressed at 15 MPa and held for 1 s to allow adjacent granules to make contact before large-scale crushing occurs. The pressure is then increased to 125 MPa at a rate of 25 MPa / s and held for 5 s. The pressure is then released at a rate of 8 MPa / s and the green body is ejected at a rate of 1.0 mm / s.
[0044] During the initial pressing process, adjacent granulated particles preferentially establish contact through the exposed area of the ceramic matrix located at the convex position, allowing part of the pressing load to be directly transferred between the alumina powders. Meanwhile, the unremoved binder surface layer continues to restrict the premature breakage of the granulated particles, thus balancing the particle integrity during the powder loading stage and the inorganic powder contact during the pressing stage.
[0045] As the pressing pressure continues to increase, the spray-granulated particles gradually deform and undergo local breakage. The alumina powder around the exposed area of the ceramic matrix interlocks with each other, forming dispersed ceramic powder connection points at the original granulation particle boundaries, and separating the potentially continuously extending binder enrichment interface into multiple discontinuous regions.
[0046] The resulting electronic insulating ceramic green body has dimensions of 50 mm × 50 mm × 0.82 mm and a density of 2.31 g / cm³. The maximum density difference measured at nine points on the same green body is 0.036 g / cm³. No edge cracking, surface indentation, or through-layer delamination was observed in the green body after demolding, indicating that the surface treatment did not significantly reduce the pressing stability of the granulated material and the integrity of the green body.
[0047] The electronic insulating ceramic green body was placed in an air atmosphere and heated to 600℃ at a heating rate of 1℃ / min to complete the debinding. Then, it was heated to 1600℃ and held for 2 hours before being cooled in the furnace to obtain an alumina electronic insulating ceramic sheet with an average bulk density of 3.72 g / cm³.
[0048] The obtained alumina electronic insulating ceramic sheet has a flatness of 0.11 mm within a length of 50 mm and a thickness range of 0.019 mm at nine points. No large pores extending continuously along the boundary of a single original granulated particle were observed in the metallographic cross-section, indicating that the ceramic powder connection formed at the exposed position can block the continuous expansion of the particle boundary pores after glue removal and reduce the influence of local pore differences on sintering shrinkage and the flatness accuracy of the ceramic sheet.
[0049] Dense ceramic particles are sintered ceramic particles with a higher degree of density than spray-granulated particles, and they do not break during rolling contact.
[0050] The particle size of the dense ceramic treated particles is larger than that of the spray granulation particles, so that after the rolling contact is completed, the dense ceramic treated particles can be separated from the treated spray granulation particles by screening.
[0051] The exposed ceramic matrix windows are spaced apart from each other, and the binder-containing surface layer between adjacent exposed ceramic matrix windows extends continuously to maintain the particle integrity of the spray-granulated particles during the conveying, loading and initial pressing processes.
[0052] During the rolling contact process, the dense ceramic treatment particles preferentially contact the convex parts of the spray granulation particles, and the rolling contact stops before the spray granulation particles disintegrate into primary ceramic powder.
[0053] In this embodiment, the dense ceramic treated particles are made from the same alumina base material and sintering aid as the spray-granulated particles. After sintering at 1580℃, their relative density is 96.8%, the particle size is controlled between 0.6 and 0.9 mm, the particle surface is round and without obvious edges. 100 particles were randomly selected before and after the rolling treatment for inspection, and no cracks or breakage were found. This can maintain a stable surface hardness when repeatedly contacting the spray-granulated particles and avoid introducing impurities of different compositions into the granulation material due to the wear of the treated particles themselves.
[0054] In this embodiment, the particle size of the spray-granulated particles is 55-125 μm, and the particle size of the dense ceramic treated particles is significantly larger than that of the spray-granulated particles. The two are added to a horizontal roller at a mass ratio of 4:1 and then rolled at 12 r / min. This allows the dense ceramic treated particles to slowly roll between the spray-granulated particles and preferentially contact the outward protruding parts of the spray-granulated particle surface. After processing, the two types of particles can be directly separated through a 300 μm sieve, avoiding the dense ceramic treated particles remaining in the subsequent granulation material for pressing.
[0055] After 5 min of rolling treatment, 30 randomly selected spray-granulated particles were observed using a scanning electron microscope. Each spray-granulated particle had 4 to 11 exposed ceramic matrix windows with separated boundaries. The equivalent diameter of a single exposed window was 7 to 24 μm, and the average proportion of exposed windows to the particle surface area was 18.6%. A continuous binder-containing surface layer was still retained between adjacent exposed windows. Therefore, the granulated particles did not form a through-layer surface peeling area. The angle of repose changed from 29.4° before treatment to 30.1° after treatment, indicating that the formation of local exposed windows did not significantly impair the flowability of the granulated material.
[0056] During the rolling process, samples were taken and observed every 1 minute. When at least 80% of the spray-granulated particles had more than 3 mutually separated ceramic matrix exposed windows on their surface, and the particle surface still retained a continuous area containing binder, and when 100 spray-granulated particles were randomly selected, the number of intact particles was no less than 96, the rolling process was stopped. In this embodiment, the above state was achieved after 5 minutes of processing. After continuing processing for 8 minutes, the phenomenon of interconnected exposed windows and increased fine powder began to appear. This indicates that controlling the processing endpoint at the stage where the convex parts of the particles are partially ground off but the main body of the particles has not yet disintegrated can take into account both the formation of ceramic matrix contact windows and the maintenance of the integrity of the granulated particles.
[0057] When separating the dense ceramic treated particles and free fine powder from the treated spray granulation particles, the dense ceramic treated particles are first removed by sieving, and then the free fine powder that has not been bound to the spray granulation particles is removed by airflow separation.
[0058] The initial pressure causes adjacent spray-granulated particles to come into contact with each other and maintains the overall outline of most spray-granulated particles; after the initial pressure, the pressing pressure is further increased, causing the spray-granulated particles to deform or break, and forming multiple ceramic powder connection positions between adjacent spray-granulated particles, which are composed of exposed windows of ceramic matrix.
[0059] In this embodiment, after the rolling process is completed, the resulting mixture is sieved through a sieve with a pore size of 300 μm. Dense ceramic particles with a particle size of 0.6 to 0.9 mm are trapped above the sieve. The treated spray granulation particles and the free fine powder generated during the rolling process pass through the sieve and enter the undersize material. The particle size difference between the two types of particles is used to separate the treated particles and prevent the dense ceramic particles from entering the subsequent molding cavity.
[0060] The undersize material is passed through the airflow separation channel in a uniform layer. The airflow direction intersects with the material falling direction, and the airflow velocity is controlled at 1.8 m / s. This allows the free fine powder with smaller mass that is not bound to the spray granulated particles to be discharged with the airflow, while the processed spray granulated particles enter the collection container below. The proportion of intact spray granulated particles observed randomly before and after airflow separation was 97.2% and 96.8%, respectively, indicating that the separation process did not cause significant secondary breakage.
[0061] The mass percentage of free fine powder with a particle size of less than 20 μm in the granulated material obtained after air separation was 0.21%, its loose density was 1.10 g / cm³, its angle of repose was 30.1°, and the relative deviation of the single powder loading mass when loading powder into the same mold cavity 10 times consecutively did not exceed 0.42%. This indicates that after removing free fine powder, the granulated material still uses whole spray-formed granules as the main flow unit, which can reduce the impact of free fine powder segregation and local accumulation during the filling process on the uniformity of green body density.
[0062] The granulated material with contact windows was loaded into a square molding cavity with a length of 50 mm and a width of 50 mm and leveled. It was initially pressed at 15 MPa and held for 1 s. Subsequently, the initially pressed sample was resin impregnated, sliced, and cross-sectionally observed. The results showed that most of the spray-formed granules still retained a recognizable overall outline. The contact between adjacent granules first occurred at the convex parts of the surface, and some contact positions were formed by the mutual contact of the exposed ceramic matrix windows of the two spray-formed granules.
[0063] The binder-containing surface layer retained during the initial pressing process can inhibit premature disintegration of granulated particles, while the exposed ceramic matrix window located on the convex part allows part of the pressing load to be directly transferred between alumina powders, thereby avoiding contact between adjacent granulated particles only through the binder-enriched surface layer, and providing an initial contact basis for the formation of ceramic powder connection positions in the subsequent main pressing stage.
[0064] After initial pressing, the pressing pressure is increased to 125 MPa at a pressurization rate of 25 MPa / s and held for 5 s, causing the spray granulation particles to gradually flatten and locally break. The alumina powder located at the contact position of adjacent particles enters the exposed window on the opposite side and its surrounding surface as the particles deform, and interlocks with each other under continuous pressure.
[0065] When the cross-section of the green body after main pressing is observed by scanning electron microscopy, multiple alumina powder connection positions can be observed at the original spray granulation particle boundary. The connection positions divide the continuous binder-containing boundary into shorter local areas, so that the granulation particles can form inorganic ceramic connections while maintaining the necessary organic bonding. This reduces the possibility of forming continuous shrinkage gaps along the original particle boundary during the glue removal process.
[0066] After the main pressing is completed, the pressure is released at a rate of 8 MPa / s, and the green body is pushed out of the mold cavity at a rate of 1.0 mm / s. No indentations caused by the residue of dense ceramic treatment particles are seen on the surface of the green body, and no loose interlayers are seen in the cross section due to the concentration of free fine powder. This indicates that sieving and air separation can ensure the stability of the composition of the granulated material entering the mold cavity, and make the subsequent pressing effect mainly generated by the exposed ceramic matrix window on the surface of the spray granulated particles.
[0067] The electronic insulating ceramic matrix is either alumina ceramic matrix or aluminum nitride ceramic matrix, and the dense ceramic treated particles are either dense alumina ceramic particles or dense aluminum nitride ceramic particles.
[0068] In this embodiment, alumina powder is used as the electronic insulating ceramic base material, and dense alumina ceramic particles made of the same alumina powder and the same sintering aid are used as the treated particles. This ensures that the trace wear particles generated during the rolling contact process of the treated particles have the same inorganic composition as the spray-granulated particles, thus avoiding the formation of local second phases or abnormal shrinkage regions during subsequent sintering due to the introduction of heterogeneous particles.
[0069] After being sintered at 1580℃, the dense alumina ceramic particles have a relative density of 96.8% and their main crystalline phase is α-Al2O3, which is consistent with the main crystalline phase of the alumina base material used in spray-granulated particles. Furthermore, their hardness and density are higher than those of spray-granulated particles, which allows them to locally grind away the binder-containing surface layer at the convex position of the granulated particles during the rolling process without causing significant breakage.
[0070] When performing elemental surface scanning on the granulated material after rolling treatment, aluminum and oxygen elements were predominant in the exposed window of the ceramic matrix and its surrounding area. No heterogeneous element enrichment introduced by the treated particles was detected, indicating that the use of dense alumina of the same system to treat the particles can maintain the consistency of the inorganic composition of the granulated material while forming the exposed window of the ceramic matrix.
[0071] After debinding and sintering, the alumina powder connection points formed at the exposed windows of the ceramic matrix are sintered synchronously with the surrounding ceramic matrix, without forming heterogeneous interfaces or abnormal grain regions at the original treatment locations. This avoids the adverse effects of the treated particles on the densification process, local shrinkage state, and insulation performance consistency of the electronic insulating ceramic sheet.
[0072] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0073] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the present invention. Various changes and modifications can be made to the present invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed.
Claims
1. A high-precision dry pressing method for forming high-performance electronic insulating ceramic sheets, characterized in that, include: Electronic insulating ceramic matrix, sintering aid and binder are mixed to form ceramic slurry, and the ceramic slurry is spray-dried to obtain spray-granulated particles with the binder on the surface; The spray-granulated particles are mixed with the dense ceramic treated particles, so that the spray-granulated particles and the dense ceramic treated particles come into rolling contact. The main crystal phase composition of the dense ceramic treated particles is the same as that of the main crystal phase composition of the electronic insulating ceramic matrix. The degree of rolling contact is controlled so that the binder-containing surface layer of the protruding part of the spray granulation particle is partially ground away to expose the electronic insulating ceramic matrix, while the binder-containing surface layer between adjacent protruding parts is retained, forming multiple mutually separated ceramic matrix exposure windows on the surface of the spray granulation particle, and keeping the spray granulation particle with an intact granulation particle shape. The dense ceramic treated particles and the free fine powder that detached during the rolling contact process were separated from the treated spray granulated particles to obtain the contact window granulated material. The granulated material with the contact window is filled into the molding cavity and initially pressed, so that at least some of the adjacent sprayed granulated particles form ceramic matrix contact through the exposed ceramic matrix window located on their respective convex parts; Continue to increase the pressing pressure to deform or break the spray-granulated particles and cause the ceramic powder around the exposed window of the ceramic matrix to interlock with each other, thereby obtaining an electronic insulating ceramic green body; The electronic insulating ceramic green body is depressurized and demolded.
2. The high-precision dry pressing method for high-performance electronic insulating ceramic sheets according to claim 1, characterized in that, The dense ceramic treated particles are sintered ceramic particles with a higher degree of density than the spray-granulated particles, and they do not break during the rolling contact process.
3. The high-precision dry pressing method for high-performance electronic insulating ceramic sheets according to claim 1, characterized in that, The particle size of the dense ceramic treated particles is larger than that of the spray granulation particles, so that after the rolling contact is completed, the dense ceramic treated particles can be separated from the treated spray granulation particles by sieving.
4. The high-precision dry pressing method for high-performance electronic insulating ceramic sheets according to claim 1, characterized in that, The exposed windows of the ceramic matrix are spaced apart from each other, and the binder-containing surface layer between adjacent exposed windows of the ceramic matrix extends continuously to maintain the particle integrity of the spray-granulated particles during the conveying, powder loading and initial pressing processes.
5. The high-precision dry pressing method for high-performance electronic insulating ceramic sheets according to claim 1, characterized in that, During the rolling contact process, the dense ceramic treated particles preferentially contact the convex parts of the spray granulation particles, and the rolling contact is stopped before the spray granulation particles disintegrate into primary ceramic powder.
6. The high-precision dry pressing method for high-performance electronic insulating ceramic sheets according to claim 1, characterized in that, When separating the dense ceramic treated particles and free fine powder from the treated spray granulation particles, the dense ceramic treated particles are first removed by sieving, and then the free fine powder that is not bound to the spray granulation particles is removed by airflow separation.
7. The high-precision dry pressing method for high-performance electronic insulating ceramic sheets according to claim 1, characterized in that, The initial pressure causes adjacent spray-granulated particles to come into contact with each other and maintains the overall outline of most spray-granulated particles; after the initial pressure, the pressing pressure is further increased to deform or break the spray-granulated particles and to form multiple ceramic powder connection positions between adjacent spray-granulated particles, which are formed by the exposed windows of the ceramic matrix.
8. The high-precision dry pressing method for high-performance electronic insulating ceramic sheets according to claim 1, characterized in that, The electronic insulating ceramic matrix is an alumina ceramic matrix or an aluminum nitride ceramic matrix, and the dense ceramic treated particles are dense alumina ceramic particles or dense aluminum nitride ceramic particles.